Total Lactic Acid Bacteria (LAB) and Antioxidant Activity of Goat's Milk Yoghurt with The Addition Of Red Bran During Refrigeration Storage - Jangnga, Indah Puspadyah; Haskito, Ajeng Erika Prihastuti; Sari, Citra; Adrenalin, Sruti Listra (Journal of Applied Veterinary Science And Technology, 2023)
Background: Goat milk yogurt is a functional food made from processed food of animal origin with the help of LAB fermentation, which is healthy for the body. The utilization of red rice bran flour as an additional ingredient in making yogurt can increase the level of antioxidant activity and become a food fiber content in yogurt. Purpose: This study aims to determine the effect of refrigerated storage temperatures (4â„ƒ) of goat milk yogurt with the addition of red rice bran flour on total LAB and antioxidant activity. Methods: Using a CRD with five treatments and four replications. The treatment included 0, 1, 2, 3, and 4 weeks of storage. Each treatment group will be calculated for total LAB using the TPC method and antioxidant activity testing using the DPPH method. The data obtained were analyzed using the One Way ANOVA Test followed by the Duncan Test to determine the effect between treatment groups. Results: The results showed that storage time significantly affected (p<0.01) total LAB and antioxidant activity. The results of total LAB successively from 0 to 4 weeks of storage were 8,0 x 108 CFU/ml, 7,8 x 107 CFU/ml, 7,6 x 107 CFU/ml, 6,4 x 106 CFU/ml, and 6,3 x 106 CFU/ml. The results of antioxidant activity successively from 0 to 4 weeks of storage were 534,29 mg/ml, 443,96 mg/ml, 358,61 mg/ml, 282,32 mg/ml, and 230,88 mg/ml. Conclusion: Goat's milk yogurt with the addition of brown rice bran flour is recommended to be consumed for up to 2 weeks of storage.